Assessment of The Impact of Tiv Spiritual Weapons of Warfare on Countering Insecurity in Nigeria - Bem, Japhet (Advances in Humanities and Contemporary Studies, 2022)
This study considers the impact of Tiv spiritual weapons of warfare on countering insecurity in Nigeria. The study sampled 382 out of the population of 75,000. The snowball sampling technique was used in selecting the subjects for the study. Mean and standard deviation statistics was used in answering the research questions. The study found that there are different types of insecurities rampaging in Nigeria such as herdsmen terrorism and violence against Christian women and children, Boko Haram insurgency, armed robbery and kidnapping among others. This is due to the fact that there is failure of security agencies in the country in the intelligence services to contain the recurring security breaches and the judiciary’s compromise of cases that concern insecurity, among other factors. It is therefore, recommended that the security agents should adapt the use of Tiv spiritual weapons of warfare such as Ikyombo í Amazar (nocturnal atomic bomb), Ivyaan í Mbatugh (nocturnal arrow), Kper ú Mbatugh (nocturnal cast net), Iyou í Mbatugh (nocturnal bees), Gberkpugh ú Mbatugh (nocturnal bullet and cut proof) and Gberkpugh ú Tan (diurnal bullet and cut proof) for countering insecurity in Nigeria